The American West at risk : science, myths, and politics of land abuse and recovery - Wilshire, Howard Gordon, 1926-; Nielson, Jane E.; Hazlett, Richard W. (Oxford University Press, 2008)
The American West at Risk summarizes the dominant human-generated environmental challenges in the 11 contiguous arid western United States - America's legendary, even mythical, frontier. When discovered by European explorers and later settlers, the west boasted rich soils, bountiful fisheries, immense, dense forests, sparkling streams, untapped ore deposits, and oil bonanzas. It now faces depletion of many of these resources, and potentially serious threats to its few "renewable" resources. The importance of this story is that preserving lands has a central role for protecting air an